Lactate-induced lactylation in skeletal muscle is associated with insulin resistance in humans - Maschari, Dominic; Saxena, Gunjan; Law, Timothy D.; Walsh, Erin; Campbell, Mason C.; Consitt, Leslie A (Frontiers in Physiology, 2022)
Elevated circulating lactate has been associated with obesity and insulin resistance. The aim of the current study was to determine if lactate-induced lysine lactylation (kla), a post-translational modification, was present in human skeletal muscle and related to insulin resistance. Fifteen lean (BMI: 22.1 ± 0.5 kg/m2) and fourteen obese (40.6 ± 1.4 kg/m2) adults underwent a muscle biopsy and 2-h oral glucose tolerance test (OGTT). Skeletal muscle lactylation was increased in the skeletal muscle of obese compared to lean females (19%, P<0.05) and associated with insulin resistance (r= 0.37, P<0.05) in the whole group. Skeletal muscle lactylation levels were significantly associated with markers of anaerobic metabolism (plasma lactate and skeletal muscle lactate dehydrogenase [LDH], P<0.05) and negatively associated with markers of oxidative metabolism (skeletal muscle cytochrome c oxidase subunit 4 and Complex I [pyruvate] OXPHOS capacity, P<0.05). Treatment of primary human skeletal muscle cells (HSkMC) with sodium lactate for 24 hours increased protein lactylation and IRS-1 serine 636 phosphorylation in a similar dose-dependent manner (P<0.05). Inhibition of glycolysis (with 2-deoxy-d-glucose) or LDH-A (with sodium oxamate or LDH-A siRNA) for 24 hours reduced HSkMC lactylation which paralleled reductions in culture media lactate accumulation. This study identified the existence of a lactate-derived post-translational modification in human skeletal muscle and suggests skeletal muscle lactylation could provide additional insight into the regulation of skeletal muscle metabolism, including insulin resistance.